Analysis Database Systems and Solve Medical Problems - Rakhimov Bakhtiyar Saidovich; Rakhimova Feroza Bakhtiyarovna; Saidova Zarina Bakhtiyar Qizi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Due to this mechanism, threshold synchronization is achieved with a minimum amount of time. It is usually designed for communication between scalar processors via shared memory. The main function of graphics processors since their inception has been graphics processing. Subsequently, after it became possible to program the processing of model vertices and pixels of rendered three-dimensional scenes using special programs (shaders), the architecture of graphic processors changed significantly. After the advent of the first general-purpose programmable graphics it became possible to process commands not only for graphic data in vector form, but also to perform ordinary calculations for arbitrary data on a variety of special cores, while implementing data parallelism.